Moldable composition

By using a composition of polyester homopolymer and softener, the problem that the existing molding composition cannot be flexible again and requires high temperature hardening is solved, and the effect of repeatable molding and hardening at room temperature is achieved, which is suitable for children.

CN119816552APending Publication Date: 2025-04-11DELTA OF SWEDEN
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380055111.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-19
Filing Date
2023-07-19
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing molding compositions cannot become flexible again after drying and harden at high temperatures, making them unsuitable for children.

Method used

A polyester homopolymer or a copolymer and a softener is used, and its melting point is in the range of 40°C to 70°C. It can deform at around body temperature and form a solid material after cooling.

Benefits of technology

The composition that can be reproducible and hardened at room temperature is achieved, suitable for children, without the need for a prolonged heating or kneading process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005250190030000051
    Figure BDA0005250190030000051
  • Figure BDA0005250190030000081
    Figure BDA0005250190030000081
  • Figure BDA0005250190030000171
    Figure BDA0005250190030000171
Patent Text Reader

Abstract

The present invention provides a composition comprising: a) at least one polyester homopolymer or copolymer having a melting point of from 40 DEG C to 70 DEG C, such as polycaprolactone; and b) at least one softening agent having a molecular weight of 50 to 500 amu, such as a carbonate, benzyl ester or benzoic acid; wherein the melting point or softening point of the composition is in the range of 30-45 DEG C. Generally, the weight of component a) accounts for 25 wt% to 95 wt% of the weight of component a) and component b); and the weight of component b) accounts for 5 wt% to 75 wt% of the weight of component a) and component b). The composition may also include a filler. The invention also provides model compounds comprising the compositions of the invention and methods of forming the compositions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to molding compositions and in particular molding compositions which are curable to a permanent shape but which can be re-softened for repeated use. Compositions which are child safe are of particular concern. Background Art

[0002] Different types of modelling clay and similar materials for making figures or sculptures have long been known in the art, both for artistic purposes on the one hand and as toys or educational materials for children on the other.

[0003] As is known, moldable or formable compositions may consist entirely of materials of the "binder" type, such as polymers, softeners and other "active" materials, or such compositions may also include inert "filler" materials which act primarily as leavening agents. Filler materials may be obtained by coating at least one filler with a layer of binder, wherein the filler is formed from particles or grains.

[0004] Polymer-based modeling clays are previously known in the art as toys or educational materials for children. EP2646996A2 discloses a game model dough composition with easy ductility and not drying, so that the model can be reshaped and the dough can be reused. An inherent disadvantage of this composition is that it cannot harden and therefore cannot be used to make toys or models to be used or decorated, railway model landscapes or aquarium decorations, etc. US5498645A discloses a moldable model dough composition, which forms a solid product after drying and can be used to make some solid articles. However, the solidification of the composition is irreversible. Therefore, once the composition is dried, it cannot become flexible again and cannot be reshaped.

[0005] WO2006101440 discloses a material composition having at least two solid phases, the softer phase being easily deformable at a temperature below the melting point of the binder, while the harder phase can be recycled back to its deformable state. A major disadvantage of this composition is that the hardened structure can only be achieved above the melting point of the binder (60-120°C. Therefore, the material must be baked in an oven or heated with the aid of a heat gun to produce a hard pattern, which is not only time-consuming but also not suitable for children and requires close supervision by adults. Another disadvantage is that if the soft material is needed again, the hard pattern must be heated and then the composition must be kneaded during the cooling process to soften it at room temperature. Again, this heating step is not suitable for children, and the latter working method requires long-term operation of the hot material, which consumes a lot of time and energy.

[0006] Generally speaking, there are two main types of known modeling compositions: those that are intended to remain ductile, and those that can be dried or cured to obtain a permanent shape. The former remain ductile and can therefore be reused, but remain soft and therefore do not produce a solid, rigid or elastic shape. This type cannot be used to produce permanent or solid objects. The latter, once formed, can be dried or cured to a rigid or elastic final shape, but cannot be readily reused because the drying or curing process cannot or cannot be easily reversed. In addition, plastic-type compositions generally require heating to cure, and therefore cannot be cured by young children without close supervision.

[0007] It would be advantageous to provide a material that could be easily formed or molded by hand, that could adopt a firm or flexible shape, and that could be further reused a potentially unlimited number of times. It would be an even greater advantage if all steps could be performed under sufficiently gentle conditions so that young children did not need close supervision to avoid the risk of injury.

[0008] Therefore, there is a need in the art to achieve a composition primarily for play and educational purposes that is easily deformable at room and blood temperatures but can be hardened and recovered at sufficiently low temperatures for children to handle without excessive processing. The composition must also have low adhesion to the surrounding environment and be aesthetically pleasing and suitable for children to use.

[0009] The inventors have surprisingly discovered a class of polymer-based compositions that undergo a sharp transition between rigidity and flexibility at around body temperature. As a result, such compositions can be reshaped at temperatures suitable for children and form a solid material after cooling. These materials can be reused without the need for long-term kneading and other intervention measures. Summary of the invention

[0010] In a first aspect, the present invention provides a composition comprising:

[0011] a) at least one polyester homopolymer or copolymer having a melting point of 40°C to 70°C; and

[0012] b) at least one softening agent having a molecular weight of 50 to 500 amu;

[0013] wherein the melting point (or softening point) of the composition is in the range of 30-45°C (e.g., 35-40°C);

[0014] wherein the weight of component a) accounts for 25 wt% to 95 wt% of component a) and component b); and

[0015] The weight of component b) accounts for 5 wt% to 75 wt% of component a) and component b).

[0016] The composition may be a pure polymer / softener composition, or may be a filled composition. Therefore, in one embodiment, the composition further comprises:

[0017] c) at least one filler.

[0018] The softening agent generally includes at least one alcohol; at least one carbonyl group; at least one ether; at least one organic acid; at least one halogen; at least one nitro group and / or at least one aromatic group.

[0019] Preferred polymers are caprolactone-based and / or lactide- or glycolide-based polyesters as described herein.

[0020] Softeners preferably include those having at least one benzyl alcohol, benzyl ester, benzyl ether and / or benzoyl moiety, including those described herein. Dibenzoate softeners are very suitable.

[0021] In one embodiment, the present invention provides a filling composition comprising components a), b) and c) as described above and further herein.

[0022] In another embodiment, the composition may include the optional components:

[0023] d) at least one silicone oil.

[0024] In another embodiment, the composition may include at least one optional component selected from:

[0025] e) Pigments;

[0026] f) Flashing agent;

[0027] g) mica or coated mica;

[0028] h) perfume;

[0029] i) Preservatives.

[0030] In another aspect, the present invention provides a method of forming a composition as described in any embodiment herein, the method comprising:

[0031] I) heating component a) to a temperature of 30 to 70° C.,

[0032] II) mixed with component b);

[0033] III) in the presence of component c) and / or components d) to h), optionally mixed with component c) and / or components d) to h); and

[0034] IV) cooling the obtained mixture to room temperature;

[0035] Wherein steps I), IIi) and III) can be carried out sequentially or simultaneously.

[0036] An exemplary embodiment in this regard comprises heating and mixing components a) and b) above the melting temperature of component a), then mixing with component c) and / or components d)-h) in the presence of component c) and / or components d)-h), and cooling to ambient temperature.

[0037] Another exemplary embodiment of this aspect, wherein component c is present, comprises mixing component c) with component b), followed by heating and mixing with component a), and cooling to ambient temperature.

[0038] In another embodiment, the present invention provides a method of forming a three-dimensional shape, comprising:

[0039] i) warming a composition as described herein in water, wherein the temperature of the water is no greater than 42°C (e.g., 35 to 42°C);

[0040] ii) forming the composition into a desired shape (e.g. by molding, extruding, rolling or freehand shaping); and

[0041] iii) cooling the composition (eg in ambient air, in ambient water, in cold air (eg in a refrigerator or domestic freezer) or in cold water, eg ice water). BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 shows the melting temperature of polycaprolactone copolymer (PCL (90%)-co-PLA (10%)) with increasing amount of softener added. The softeners used were dipropylene glycol dibenzoate and benzoic acid ester (Benzoflex 988). DETAILED DESCRIPTION

[0043] The present invention provides a moldable or ductile composition which can be formed at slightly elevated temperatures but will become rigid and / or elastic upon cooling to room temperature. Such a composition may consist solely of polymer and softener materials (plus optional additives), or may include polymer, softener and filler (plus optional additives).

[0044] Component a) of the composition is at least one polyester polymer, suitable polymers include homopolymers and / or copolymers, and the melting point is generally 42 to 70°C. The melting point range preferably includes 45 to 65°C or 48 to 62°C. A particularly suitable melting point range is 52 to 63°C. The average (preferably weight average) molecular weight of the polymer of component a) is generally 5 to 200 kD, such as 10 to 100 kD, preferably 25 to 100 or 25 to 50 kD. The melt flow index of the polymer of component a) may be 2 to 100 g / 10 min, preferably 3 to 70 g / 10 min, for example 5 to 10 g / 10 min. MFI is generally measured according to ASTM D1238 and / or ISO 1133. The typical temperature for measuring the MFI of component a) is 80°C for polymers with a molecular weight below 50 KD (e.g. 35 KD and below, preferably 25 KD and below), or 160°C for polymers with a molecular weight above 25 KD (e.g. above 35 KD, preferably 50 KD and above).

[0045] Suitable polymers for component a) include homopolymers and copolymers. Both can be formed or made from caprolactone monomers. In particular, in one embodiment, the polymer of component a) can include, essentially include, or consist of at least one polycaprolactone homopolymer. In another embodiment, component a) can include, essentially include, or consist of at least one polycaprolactone copolymer. Such copolymers are typically formed or made with another polyester material and / or by another ester or alcohol functionalized organic acid. Suitable alcohol functionalized organic acids that can form suitable comonomers include lactic acid and / or glycolic acid, or any acid of the following formula (II).

[0046]

[0047] wherein each R5 and R6 are each independently selected from H, CH3, C2 to C8 branched or straight chain alkyl or alkenyl; and

[0048] m is 1 to 8, preferably 1 to 5

[0049] Lactic acid (m = 1, R5 = H, R6 = CH3); and

[0050] Glycolic acid (m=1, R5=H, R6=H)

[0051] is a preferred embodiment.

[0052] When using caprolactone copolymer, preferably at least 50wt% (e.g., 50 to 90wt% or 50 to 95wt%) of the monomers are caprolactone, and the remainder is one or more other monomers of formula II. Preferably, the caprolactone content is at least 60% or at least 75%, preferably at least 85%. Accordingly, the non-caprolactone monomers of formula II account for about 2 to 50wt%, preferably 4 to 30wt% or 5 to 20wt% of the polymer.

[0053] Preferred homopolymers are caprolactone homopolymers.In one embodiment, component a) may comprise, consist essentially of, or consist of at least one caprolactone homopolymer.

[0054] The copolymer is preferably a copolymer of caprolactone and lactide (e.g. 60 to 95 wt% caprolactone and 5 to 40 wt% lactide). In one embodiment, component a) may comprise, consist essentially of, or consist of at least one copolymer of caprolactone and lactide.

[0055] In all aspects of the invention, the polyester homopolymer or copolymer used as component a) can have any suitable molecular weight. Typical number average molecular weights can be 3,000 to 200,000, preferably 10,000 to 120,000 or 20,000 to 100,000. In one embodiment, polymers with molecular weights of about 40,000 to 80,000 are used.

[0056] The content of polymer component a) is usually at least 25 wt% of components a) and b). For example, it can be 28 wt% to 95 wt%, 30 wt% to 70 wt% or 32 wt% to 65 wt% of components a) and b).

[0057] For homopolymers and copolymers in all aspects of the invention, the ends of the polymers may be substituted with any suitable functional groups. This may be to adjust the properties or reactivity of the polymer, or may be a result of the polymerization process. In particular, at least one end of the polymer chain may include the residue of any suitable initiator. Common residues of initiators include substituted esters (such as diol esters, such as C2-C8 diols). These are particularly common at the acid ends of polyester chains. Diols particularly useful as initiators include ethylene glycol, propylene glycol and butanediol or pentanediol. Butanediol esters are particularly common at the ends of polyesters.

[0058] The compositions of all aspects of the invention comprise a softener component b). Such a softener may be any suitable material which serves to reduce the melting point (or melting point range) of the polymer component a) so that it meets the ranges discussed herein. Suitable softener materials typically include at least one functional group, especially at least one oxygen-containing functional group. Suitable softeners typically include at least one alcohol; at least one carbonyl group (e.g., carbonate, ketone, aldehyde, or ester); at least one ether; at least one epoxide; at least one organic acid; at least one halogen; at least one nitro group and / or at least one aromatic group. Many aromatic groups are suitable, but benzyl is a typical effective group. Terephthalate groups include "benzoic acid" type functional groups and are also very suitable, particularly in the form of esters, for example with C2 to C 12 Diesters of alkanols.

[0059] Alcohols including polyols can form effective softeners as all or part of component b). They can include C2 to C 12 The diols and diol oligomers (such as diethylene glycol or triethylene glycol or dipropylene glycol or tripropylene glycol) of the present invention can be mixed with one or two organic acids (especially C2 to C 12 alkyl organic acid) to form a monoester or a diester.

[0060] Organic acids, including dibasic acids (e.g. C2 to C 12 Organic dibasic acids) can also form suitable softening agents and can be used as free acids with suitable alcohols (e.g., C2 to C 12 Alkyl alcohols or diols) are used as monoesters or diesters, or as oligomers with C2 to C8 alkyl diols such as ethylene glycol or propylene glycol. Fatty acids, such as C6 to C 20 Fatty acids and their esters (eg, esters of C2 to C6 alcohols, including diols and polyols, such as glycerol).

[0061] "Carbonates" (compounds having a carbonate moiety), such as propylene carbonate, may also form suitable softening agents as all or part of component b). Suitable carbonates include cyclic or linear alkyl carbonates and / or aryl carbonates, such as cyclic alkylene carbonates (e.g., C2 to C 12 Cyclic carbonates), linear alkyl carbonates such as R5-O-CO-O-R6, wherein R5 and R6 are independently C1 to C 12 Linear branched alkyl carbonate or aryl carbonate, such as R7-O-CO-O-R8, wherein R7 and R8 are independently C5 to C 10 Aryl or heteroaryl, such as phenyl. Dicarbonate such as C2-C 12Dialkyl dicarbonates (e.g. dimethyl dicarbonate or diethyl dicarbonate) may also be suitable. Examples of suitable carbonates include diphenyl carbonate, ethylene carbonate, trimethylene carbonate, demethyl carbonate, propylene carbonate and mixtures thereof. The carbonate is preferably propylene carbonate.

[0062] In a preferred embodiment, component b) may comprise or consist of at least one carbonate. In a further preferred embodiment, component b) may comprise, in addition to another softener, at least one carbonate, such as a benzyl ester (eg as described herein).

[0063] In one embodiment, the softener may include at least one benzyl alcohol, at least one benzyl ester, at least one benzyl ether and / or at least one benzoyl moiety. All aromatic groups, including benzyl, may optionally be substituted with at least one alcohol, at least one carbonyl, at least one ether, at least one organic acid, at least one halogen and / or at least one nitro group. Alkyl and / or alkenyl groups may also form substituents on any aromatic group, including benzyl. Suitable alkyl and / or alkenyl groups may include, for example, linear, branched or cyclic C1 to C1 12 Alkyl and / or alkenyl, preferably C1 to C4 alkyl and / or alkenyl. Obviously, alkenyl has at least 2 carbon atoms, and cyclic groups have at least 3 atoms in the ring.

[0064] A very suitable component which may form all or part of component b) is a dibenzyl, preferably a dibenzyl ester linked via a polyalkylene oxide chain. Suitable compounds include at least one compound selected from the following formula (i):

[0065]

[0066] in:

[0067] R1 and R2 are each independently selected from H, Cl, F, Br, NO2, CH3, C2 to C8 branched or straight chain alkyl or alkenyl;

[0068] Each R3 and R4 is independently selected from H, Cl, F, Br, CH3, C2 to C8 branched or straight chain alkyl or alkenyl;

[0069] m is an integer value between 1 and 10;

[0070] and n is an integer value between 1 and 10;

[0071] In a preferred embodiment, R1 and R2 are each independently selected from H, CH3, C2 to C4 branched or straight chain alkyl or alkenyl.

[0072] In another embodiment, each of R3 and R4 is independently selected from H, CH3 and C2 to C4 branched or straight chain alkyl.

[0073] In another embodiment, at least one of R3 and R4 is H, preferably each of R3 and R4 is H.

[0074] In another embodiment, m is an integer value between 2-3.

[0075] In another embodiment, n is an integer value between 2-3.

[0076] The weight of the softener component b) is usually up to 75 wt% of components a) and b). For example, it can be 5 to 75 wt%, 30 to 70 wt% or 35 to 68 wt% of components a) and b).

[0077] The softener component b) generally has a sufficiently high boiling point to prevent substantial loss of the softener by evaporation. In one embodiment, the softener may have a boiling point greater than 150°C (eg, 150 to 1000°C), preferably greater than 200°C or greater than 220°C.

[0078] The compositions of the present invention (and all aspects thereof) may include a filler material. This filler is different from the "binder" material of components a) and b) in that its melting point does not have to be controlled. When the binder material softens, the composition will also soften, but the binder material may contain an inert filler material that does not need to participate in such a transition to make the overall composition ductile. The filler component is referred to herein as component "c)".

[0079] When filler component c) is present, it is at least partially coated and encapsulated by components a) and b).

[0080] The filler (component c)) can be any suitable inert material, but is typically a particulate material. Suitable materials include sand, glass and other "inorganic" materials, such as minerals; and polymers, including natural, semi-synthetic and synthetic polymers. Natural polymers may include fillers based on polyphenols and polysaccharides, including lignin and cellulose-type fillers such as wood chips, and carbohydrate-type fillers such as wheat flour, rice flour or corn flour. Synthetic polymers include polyolefins (such as polystyrene, polyethylene or polypropylene), polyesters (such as polyethylene terephthalate (PET), polybutyrate), polyamides, polyurethanes, etc. and mixtures thereof. Expanding materials include hollow glass microspheres and expanding polymers (polymer foams), such as foamed latex, polyurethane forms, expanded PVC, expanded polystyrene or expanded polyethylene, and copolymers including any of these materials. A particularly suitable expanding material is "Expancel", which is a copolymer of vinyl chloride, acrylonitrile and methyl methacrylate, usually formulated with isobutylene as a blowing agent.

[0081] In one embodiment, the filler material can be a biodegradable material, such as a polyester (e.g., polylactide). In this case, the melting point of the filler polyester will generally be higher than the melting point when the adhesive components a) and b) are combined together. For example, the melting point of the filler is 50° C. or higher (e.g., 50 to 200° C.). Polylactide polymers, polyglycolide polymers, or lactide / glycolide copolymers are all suitable embodiments. Such polymers can be used as solid polymer particles or as expanded foam particles such as expanded foam beads. Such expanded beads can be formed using known methods, such as using alkanes, air, or CO2 blowing agents. BEWI's BioFoam is an embodiment of a suitable polyester foam filler. For such foams, the particle size can be any size indicated herein, such as 0.5 to 5 mm.

[0082] Typically, the melting point of the filler material is higher than that of the binder material. Some fillers (e.g., glass or mineral fillers) will not melt under actual use conditions, but polymer fillers (especially synthetic polymer fillers) typically have a melting point or decomposition temperature of at least 70°C (e.g., 70 to 500°C, such as 70 to 150°C).

[0083] Typical examples of filler component c) include sand fillers, glass fillers, polymer fillers, mineral fillers or mixtures thereof. Typical sand fillers include quartz sand and / or silica sand. Therefore, this "sand" may include particles of ordinary sand or gravel size. As noted herein, the average particle size of typical "sand" is 50 μm to 5 mm (e.g., 63 μm to 5 mm), preferably 95 μm to 3 mm, but sand can also include gravel and pebble fillers with an average particle size of up to about 10 mm. When referring to a single particle, the size is usually the smallest diameter (i.e., the diameter on the smallest axis). Sand fillers (and all other fillers) may be "bimodal" or "multimodal" because fillers of various sizes may be present. For example, fine sand or silica fillers with an average particle size of less than 100 μm can be used in combination with ordinary "sand" or gravel fillers with a particle size of 1 mm or more (e.g., 1 to 10 mm). This bimodal mixture of fillers allows for better coating of larger particles and can improve the performance of the adhesive. Typically in this case, when the densities of the two sizes of filler particles are similar (eg ±50%), the filler component c) will comprise at least 60 wt% of the larger size filler, preferably at least 75 wt%.

[0084] Very suitable "small" fillers are finely powdered calcium carbonate or silica. This filler has little effect on the texture of the material, but can increase the volume of the adhesive component. The average particle size of this type of finely powdered filler ("small filler") may be less than 20 μm (e.g. 0.5 to 20 μm), preferably less than 10 μm (e.g. 1 to 10 μm). An average particle size of 0.5 to 8 or 2 to 20 μm is very suitable for this small filler, which can be formed from any filler material disclosed herein, especially inorganic fillers such as silica or calcium carbonate. Such small filler particles may be the only filler, but may also be used in combination with larger filler materials. All filler content ranges discussed herein are suitable, but for small filler particles, it is preferred that it accounts for about 10 to 50 wt %, especially 20 to 40 wt % of all components in the composition.

[0085] Silica fillers, especially hydrophobic silica fillers, form very preferred mineral fillers for use as "small fillers", forming at least part of component c) of the present invention. Such fillers are added in an amount of about 1 to 30% by weight of all components in the composition. This pre-filled composition is then added to a larger amount of another filler (see below for typical amounts of fillers), which small filler has the effect of increasing volume and may also have the binding effect of components a) and b), without the need for more polymer or softener.

[0086] In an advantageous embodiment, the various products of the present invention may include both a "small filler" (such as a hydrophobic fumed silica filler or a small particle calcium carbonate filler) and a second filler of any type described herein. This provides advantages for the elasticity and firmness of the adhesive, particularly when the small filler (such as a hydrophobic fumed silica filler) is used in an amount of about 5 to 30 wt% (e.g., 10 to 25 wt% or 5 to 15 wt%) of the total of the filler and components a) and b). Preferred hydrophobic fumed silica fillers may include various particle sizes, including aggregates of small particles. The minimum size of typical aggregated fumed silica particles may be in the range of 1 to 100 μm, preferably about 5 to 50 μm.

[0087] All fillers, particularly mineral fillers, including glass, sand, silica, alumina and other mineral fillers, can be surface treated. There are many useful surface treatment methods that can improve various properties, such as performance and / or appearance. A preferred surface treatment is a hydrophobic surface treatment to "hydrophobize" the surface of the filler. Thus, surface treated (e.g., hydrophobized) glass, sand, silica and / or alumina form preferred fillers in the present invention. Suitable surface treatments, particularly for silica-containing fillers, can include treatment with 0.05 to 0.2 wt % of an alkoxysilane or silylalkanoate.

[0088] Glass fillers useful as component c) in all aspects of the invention include cullet fillers, glass sphere fillers, hollow glass sphere fillers, and mixtures thereof. The average particle size is preferably about 10 μm to 2 mm, although the cullet filler may include very small particles, for example down to 1 μm or less.

[0089] In all aspects of the invention, certain mineral fillers are very advantageous as all or part of component c). Such mineral fillers include sand (as described above), silica fillers, titanium dioxide fillers, aluminum oxide fillers, calcium carbonate fillers, calcium sulfate fillers, sodium sulfate fillers, silicate compounds, kaolin and other clays, calcium phosphates, talc and mixtures thereof.

[0090] The polymer filler can include any suitable form of compatible natural, semi-synthetic or synthetic polymers.Synthetic polymer fillers include, for example, polyolefins (e.g., polystyrene, polyethylene, polypropylene), polyesters and / or polyamide fillers, including beads, wood shavings, polymer sawdust, cut film or any other suitable particles of such materials.Preferred filler particles are beads, and synthetic polymer fillers can include polystyrene beads, other polyolefin beads, polyester beads and / or polyamide beads.This polymer filler can be in the form of a solid block, or can be formed into expanded open-cell or closed-cell foams by methods well known in the art.This "expanded" material can become an excellent filler, particularly in places where lightweight or insulating materials are needed.This lightweight material includes hollow spheres of any polymer indicated herein and "expanded" foam materials, including expanded polystyrene, expanded polyolefins, expanded polyesters, expanded polyamides, expanded PLA (polylactide) and mixtures thereof, usually in the form of foam beads.The size of the polymer filler particles can vary, with a diameter from about 50 μm to several mm (e.g., up to about 10 mm). Generally speaking, unexpanded or unfoamed fillers usually have smaller particle sizes (e.g., 50 μm to 1000 μm, preferably 100 μm to 500 μm), while expanded or foamed fillers usually have larger particle sizes, e.g., 200 μm to 10 mm, preferably 300 μm to 5 mm). As with other particle sizes described herein, where the context permits, the particle size generally refers to the smallest size.

[0091] The polymer filler may also include or be composed of natural polymers, such as polysaccharides including starch, chitin and cellulose, and other natural polymers such as polyphenols (e.g. lignin) and proteins (e.g. keratin). Polysaccharides are particularly suitable, and may be, for example, in the form of powder ground from natural materials such as cereals (e.g. wheat, corn, rice), or powder, dust or debris from wood, bamboo or other fibrous materials. Natural materials may also be "expanded" by heating to generate materials such as popcorn, puffed wheat or crisp rice. Steam expansion or steam explosion may also be used. These materials may also be used as fillers of the present invention, whether natural large particles or small particles ground or cut. Natural polymers are generally very nontoxic and safe to use, and are very useful in embodiments of the present invention that may be used by children. Sawdust and fine wood chips, wheat, corn, wood and rice flour are preferred natural polymer fillers. Among the various materials of the present invention, charcoal from natural sources may be used as a filling material or as a black colorant.

[0092] The total amount of filler in the composition of the present invention may be from about 1 wt % to 99.5 wt % of component c) of the total composition. In practice, two sub-ratios are most likely to be used, depending on the type of filler used and the density of the filler. For non-expanding fillers (e.g., with a density greater than 0.5 g / cm 3 ), the total amount of filler can be about 10wt% to 99.5wt% of component c) of the total composition. Preferably, in the total composition, the total ratio of components a) and b) to component c) in all components is about 2 to 30wt% binder and 70 to 98wt% filler. For expanding fillers (e.g., with a density of less than 0.5g / cm 3 The filler (component c)) and the binder (components a) and b)) should not be greater than about 500:1 by volume, preferably not greater than 200:1 by volume. Common ratios may be between 100:1 and 1:1, for example, between 50:1 and 2:1 or between 40:1 and 5:1.

[0093] Optional component d) is applicable to all aspects of the present invention and is related to silicone fluids (silicone oils). Such silicone fluids are generally linear, branched and / or cyclic oil-based or polyalkylsiloxanes with or without at least one hydroxyl terminal. Preferred examples are polydimethylsiloxanes or oligodimethylsiloxanes with or without at least one hydroxyl terminal.

[0094] Suitable silicone fluids have a wide range of viscosities, for example, 1 to 5000 mPas at 25°C. Preferably, the viscosity is about 2 to 2500 mPas at 25°C (e.g., 2 to 150 mPas at 25°C). Suitable oligo- or poly-alkylsiloxanes may have a molecular weight ranging from about 100 D to about 50 kD, for example, about 0.2 to about 30 kD or 0.2 to 5 kD. Polydimethylsiloxane (PDMS) is very suitable, with any terminal groups (including hydroxyl-terminated and / or non-hydroxyl-terminated PDMS).

[0095] Some examples of useful silicone fluids include CDS100 (a linear polydimethylsiloxane terminated with hydroxyl groups at both ends, with a molecular weight of about 4 kD and a viscosity of about 100 mPas at 20°C), AK5 (a low molecular weight oligodimethylsiloxane without hydroxyl groups, with a viscosity of about 5 mPas at 25°C), AK10 (Wacker, a polydimethylsiloxane without hydroxyl groups, with a molecular weight of about 1100 D) and polymer C 2T (Wacker, a linear polydimethylsiloxane terminated with hydroxyl groups at both ends, with a molecular weight of about 25,000 and a viscosity of about 2000 mPas at 25°C).

[0096] If component c) is present, the content of component c) is generally not more than 20 wt% (e.g. 0.5% to 20%) of the total composition. Preferably, it is 1 to 15 wt% or 3 to 12 wt% (e.g. 5 to 10%). The amount of silicone oil (if present) can reach about 15 wt% (e.g. 0.1 to 15 wt%) of components a) and b), preferably 1 to 12 wt%, for example 2 to 10 wt%, relative to the adhesive components a) and b).

[0097] In all aspects of the invention, the products and compositions may include at least one of a variety of optional components, such as:

[0098] e) Pigments;

[0099] f) Flashing agent;

[0100] g) mica or coated mica;

[0101] h) perfume;

[0102] i) preservatives; and / or

[0103] j) Flame retardants.

[0104] Each optional component provides useful and valuable advantages in certain embodiments and certain applications, and can be independently selected and used alone, or in any combination where technically feasible. For clarity, various components are described separately herein, but can be used in combination to provide the desired properties for the compositions of the present invention.

[0105] Examples of each of these additives are well known to the skilled artisan, and many are illustrated herein. In preferred embodiments, these optional components can be any of the components listed in the Examples section herein, and particularly in the "Chemical Table Used in the Examples" preceding the specific examples. The glitters described herein include glitters based on plastic films (e.g., polystyrene film glitters).

[0106] If components e) to j) are present, the additional components e) to j) or other additional components generally comprise no more than 5 wt% (e.g. 0.01 to 5 wt%) of the total composition, respectively. Preferably no more than 2 wt% or no more than 1 wt%.

[0107] The present invention also provides a method for forming a three-dimensional shape from the composition of the present invention. Such a method preferably requires only very mild conditions so that people of all ages can use it, with little risk and requiring only minimal supervision. In general, the composition of the present invention is formulated to soften at or near body temperature, so that it can be heat softened and handled in a softened state without the risk of burns. Water is an efficient heat transfer medium and can be used for this purpose. For example, warm water can be provided in a low-power constant temperature heating bath and maintained at a safe temperature sufficient to soften the composition. Suitable temperatures do not exceed 45°C, preferably do not exceed 42°C (e.g., 35 to 42°C).

[0108] Accordingly, the melting point (softening point, e.g., where fillers prevent assessment of the melting point) of the composition of the invention is from 30°C to 40°C, e.g., from 35°C to 40°C or from 36°C to 39°C. The melting point can be assessed using a standard "hot stage" method. In all appropriate embodiments, particularly where the melting point of the composition is not easily assessed (e.g., due to the presence of solid fillers), "melting point" as used herein is understood to mean "softening point". The softening point can be measured by any appropriate method, e.g., preparing a 100×10×3 mm rod of the composition and cooling it to room temperature, then supporting the rod at 1 cm at each end at a controlled temperature, and measuring the temperature when the center of the rod sags 5 cm or more under gravity. This test is independent of the thickness of the rod, so when using large particle fillers, a rod of at least two filler particle thicknesses can be used.

[0109] The composition can be repeatedly heated and formed until the final form is achieved, at which point the composition can be cooled. Cooling can be done simply by placing the three-dimensional shape in room temperature air or cold air (e.g., a refrigerator or household freezer), or by immersion in room temperature water or cooled water. Ice water can essentially "freeze" the composition of the present invention instantly. Rapid freezing can also be achieved in a refrigerator or household freezer.

[0110] In one embodiment, the composition of any aspect or embodiment of the present invention remains moldable at a suitable temperature (e.g., 35 to 42° C.). The composition of the present invention preferably does not "set" or "cure." That is, the composition of the present invention does not form a rigid material that cannot be reshaped by hand at a suitable temperature (e.g., 35 to 42° C.).

[0111] As used herein, the terms "about", "around", "substantially" or "approximately" in relation to numbers or numerical ranges generally indicate that the specified number or range is preferred, but that the number may vary within a certain range without having a substantial effect on the performance of the relevant material, composition or similar product. The skilled person can generally easily determine the extent to which these numbers can be varied without impairing the key advantages of the invention. As a general guide, these numbers or the ends of these ranges may vary by ±10%, preferably ±5%, and more preferably ±1%. For compositions that are "mainly composed of" certain components, a corresponding meaning may also be given, which may include up to 10%, preferably up to 5%, and most preferably up to 1% of other components in addition to the specified components. When a chemical group, chain or other part described herein is optionally substituted, such substitution may be absent, or one or more atoms (usually one or more hydrogen and / or carbon) in the part may be substituted by groups such as halide (e.g., F, Cl, Br, I) groups; oxygen groups such as ethers, alcohols, esters, carboxylic acids or epoxides; nitrogen groups such as amines, amides, nitrile or nitro groups; or sulfur-based groups such as thiols, disulfides, thioesters, etc. Where the context permits, up to about 10 such substitutions may be made, but typically 3 or a few substitutions are made, for example 1, 2 or 3 substitutions are typically independently selected.

[0112] Example

[0113] These examples show that standard grades of polycaprolactone polymers and copolymers can be effectively used in the present invention. By combining the polymer and the softener, we obtain a composition with stable, reproducible and controllable properties. The addition of the softener can be used to control and adjust the properties in a reproducible manner.

[0114] Materials and performance

[0115] Table 1: Various softeners used in the examples.

[0116]

[0117] Table 2: Various fillers used in the examples.

[0118]

[0119] Table 3: Various pigments and additives used in the examples.

[0120]

[0121] Example 1: - Polyester homopolymers and copolymers

[0122] The melting temperature was studied as a function of lactide content (Table 4) and the temperature of the polymer samples was controlled with the aid of a hot stage. The melting temperature was determined visually and was the temperature at which the polymer matrix changed from opaque / white to transparent / translucent and from solid to ductile.

[0123] The first observation is that the lower molecular weight of the (homo)polymer appears to lower the melting temperature.

[0124] The lactide content in the copolymer was expanded to include non-commercial samples in order to investigate the melting temperature over a wider range of lactide content. The batches vary greatly and result in a scatter in the data, and the melting point temperature varies for the same lactide content in different production batches. As a rough general observation, the melting temperature of poly(caprolactone-co-lactide) polymers decreases by approximately 1°C per % lactide in the copolymer. The decrease in melting temperature quickly levels off with increasing lactide content, with the lowest melting temperatures observed being in the 40°C to 45°C range. The melting temperature of caprolactone homopolymers is approximately 60°C and that of polylactide homopolymers is approximately 170°C. Therefore, the melting temperature of the copolymer as a function of lactide content passes through a minimum.

[0125] Table 4: Homopolymers and copolymers with lactide contents ranging from 0 to 15%.

[0126]

[0127] Example 2: - Softener

[0128] Table 5 tests 13 different softeners and evaluates the melt temperature and material properties of PCL homopolymer-based blends.

[0129] Judging by the combination of melting point depression and mechanical properties, the best softeners appear to be Benzoflex 988 and Benzoflex 2088 at 40% addition. Benzoflex 988 or Benzoflex 2088 were evaluated at higher addition levels (50% and 60%). In fact, the melting temperature was further reduced (41°C and 37°C). Despite the higher addition level, the mechanical properties of PCL (high Mw) in the solid state are acceptable, while the samples prepared with PCL (low Mw) are more significantly negatively affected, with a softer, more brittle matrix in the solid state and more viscous properties in the molten state.

[0130] According to the results in Table 5, a mixture of 50% CAPA 6500D (high weight average molecular weight (high Mw) polycaprolactone), 40% Benzoflex 988 and 10% Edenol 1200 was evaluated as a possible alternative. It was found that the melting temperature was about 44°C and the material properties were not ideal. Therefore, in this case, pure Benzoflex 988 seems to be a better choice than combining two promising softeners.

[0131] Table 5: Mixture of solvent (40%) and PCL (high weight average molecular weight) (60%) from different suppliers / manufacturers. After solidification, the melting temperature was evaluated on a hot stage and the material properties were subjectively assessed.

[0132]

[0133] Example 3: – Polymer / Softener Optimization

[0134] Based on the results of Examples 1 and 2, the change in the melting temperature of PCL(90)-co-PLA(10) after the addition of Benzoflex 988 was studied and optimized. The samples were prepared by melting and mixing the polymers and softeners. The transition of the solid sample from opaque / white to transparent / translucent and from solid to ductile defined the melting temperature and was measured by the hot stage. Figure 1 shows that when the content of Benzoflex 988 reached about 40wt%, the melting temperature of the mixture dropped sharply and then leveled off at about 35°C.

[0135] Similar behavior was found in PCL (high weight average molecular weight (high Mw)) homopolymer, i.e., when the content of Benzoflex988 was 0wt%, 40wt%, 50wt%, 60wt% and 64wt%, the melting temperatures were 60°C, 45°C, 41°C, 37°C and 37°C, respectively.

[0136] Adding Benzoflex 988 appears to be a convenient and reproducible way to provide a mixture with an optimal melting temperature of about 35° C. to 37° C. In this way, a "simpler" homopolymer can be used instead of a more complex copolymer when a melting temperature close to body temperature is required.

[0137] Example 4: - Filling composition

[0138] Four different model compounds were prepared using the polymer PCL(88)-co-PLA(12), see Table 6. The melting temperature was lowered and controlled at around 39°C by the balanced addition of softener (Mixture 1).

[0139] Microlene requires about 85°C to disperse evenly. To prepare mixture 2, PCL(88)-co-PLA(12) and Microlene (blue) were first mixed at about 85°C. Benzoflex 988 was added and mixed well before adding Iokalit A and then AK5.

[0140] To prepare mixture 3, lower temperatures can be used. Mixing can be done at a temperature slightly above the melting temperature of the polymers. PCL(88)-co-PLA(12), Lysopure (red), and Benzoflex 2088 are mixed at a temperature of about 50°C. Iokalit A is then added, followed by Geoglit Silver and AK5.

[0141] Mix 4 contained more filler, while the mixing followed the same preparation sequence as Mix 3.

[0142] The resulting model compound can be hand-shaped and sculpted at a working temperature of about 39°C above its melting temperature. The material settles and solidifies at normal room temperature. Mix 4 is a cheaper formulation because it contains cheaper fillers. The higher the filler content, the more brittle and less flexible the cured compound will be.

[0143] Table 6: Formulations of four model compounds filled with small inorganic fillers (lokalit A-CaCO3).

[0144] raw material Mixture 1 Mixture 2 Mixture 3 Mixture 4 PCL(88)-co-PLA(12) 69% wt 41%wt 40.6%wt 26%wt Lysopure(red) - - 0.2%wt - Microlene (blue) - 0.5%wt - - GWT (green) - - - 1%wt Geoglit Silver - - 1%wt - Benzoflex 988 31%wt 18% wt 18% wt 12%wt Iokalit A - 35% 34.7% 57% wt AK5 - 5.5%wt 5.5%wt 4%wt

[0145] Example 5:- Using different grades of sand filler

[0146] Different sizes of sand can be used to obtain model compounds, see Table 7. Mix 5 optimizes the ratio of PCL (high weight average molecular weight (high Mw)) and Benzoflex 988 to achieve a balance between physical properties (strength of the solid compound) and melting temperature (37°C). Mix 6, Mix 7 and Mix 8 all have a melting temperature of about 37°C, above which they can be easily hand-molded. At lower temperatures, the material will precipitate and solidify. By repeating the temperature cycle, the material can be reshaped into a new solid object. Due to the different sizes of the sand particles, the texture of the material varies from "soft and smooth" to more "rough and grainy".

[0147] The commercial sand raw material must first be surface treated to make it suitable for use with the adhesive. First, an aqueous dispersion containing the two silanes is prepared: a mixture of the silanes Wacker Geniosil XL10 (4.5 g) and WackerSilres 1701 (0.5 g) is added to an aqueous solution of 94.5 g water and 0.5 g HAc (24%) under vigorous stirring to form a dispersion. Stirring (vigorous) is continued for about 30-60 minutes. At the same time, the sand GA39, M32 or B55 is heated to about 55-60°C in a stainless steel tank. Under continuous stirring, the aqueous silane dispersion ((100 g)) is added to the hot sand. Stirring is continued until the water evaporates and the sand becomes dry. This process provides surface treated sand GA39 (ST), M32 (ST) or B55 (ST), which is used as a filler.

[0148] Table 7: Formulations of four model compounds filled with sand fillers of different sizes.

[0149]

[0150] Example 6: - Compositions containing expanded polymer fillers

[0151] Filled model compounds were obtained with (expanded) polymer fillers of different sizes, see Table 8. The ratio between PCL (high weight average molecular weight (high Mw)) and Benzoflex 988 was the same as in Example 5, with a melting temperature of about 37°C. Above this temperature, the model compounds in Table 8 can be easily molded by hand. At lower temperatures, the material will precipitate and solidify. By repeated temperature cycles, the material can be reshaped into a new solid object. Due to the different sizes of the fillers, the texture of the materials also varies. Mixtures 9 and 10 have a soft / elastic texture due to the voids or hollowness of the fillers. Mixture 11 has a higher ratio of binder to filler, and the texture of the material in the solid state is more like a plastic material.

[0152] Table 8: Formulations of four model compounds filled with expanded polymer-based fillers of different sizes.

[0153]

[0154] Example 7: - Compositions containing polymer fillers and in-situ expansion

[0155] Heating Expancel 461 DU to a temperature of about 100°C causes the filler polymer shell to soften. The added blowing agent expands to form particles similar to Expancel 461DE.

[0156] PCL (low weight average molecular weight (low Mw)) and Benzoflex 988 were first mixed at a temperature of about 65°C, and then Expancel 461DU was mixed therein to prepare a mixture containing 63%wt PCL (low weight average molecular weight (low Mw)), 27%wt Benzoflex 988 and 10%wt Expancel 461DU. The PCL-based binder of this material melts at a temperature of about 50°C, and the material becomes ductile.

[0157] When a small piece of solid material containing Expancel 461DU comes in contact with boiling water, first the PCL (low Mw) based binder melts and then the blowing agent expands the filler particles in situ after the polymer shell softens due to the temperature increase. The resulting material is a lightweight material with properties very similar to similar materials prepared using pre-expanded Expancel 461DE. Low Mw PCL polymer was initially chosen because the high melt flow index (MFI) facilitates the in-situ expansion of Expancel. The disadvantage of low Mw is that the material is more likely to stick to hands and the surrounding environment during the molten stage.

[0158] A similar formulation was prepared with PCL (high Mw): 63%wt PCL (low Mw), 27%wt Benzoflex 988 and 10%wt Expancel 461DU. Like the low Mw polymer based blend, this formulation also swelled in hot water, albeit with a lower MFI. Both formed effective compositions.

[0159] Example 8: – Using two types of fillers

[0160] Small size fillers can be added to the binder system with limited (essentially negligible) impact on the final material properties. In Mix 13, the amount of PCL (high Mw) and Benzoflex 988 was reduced by 25 wt% (from 6% wt to 4.5% wt and from 9% wt to 6.7% wt) using HDK H2000. This is an effective way to reduce the expensive polymer content without affecting the material properties too much.

[0161] Table 9: Formulations of two model compounds filled with sand M32 (ST)

[0162]

[0163] Example 9 - Using Carbonate as Softener

[0164] While DMC appears to be a suitable softener as it mixes easily with PCL (high Mw) when melted in all evaluated proportions up to 50%, its compatibility is hampered by its low boiling point and consequent high vapor pressure. This results in rapid loss of DMC, especially when heated. However, PC has a much higher boiling point than DMC and is therefore a more attractive alternative. After mixing the PC softener with PCL (high Mw) in the molten phase, the mixture was either cooled to solidify quickly or slowly cooled to solidify over a longer period of time. The melting temperatures of the various mixtures were evaluated with the aid of a hot stage and an infrared thermometer.

[0165] Table 10: Melting points of mixtures including different ratios of PCL and PC after rapid cooling and observations after slow cooling.

[0166]

[0167] Slow cooling appears to result in the separation of a small fraction of the solvent at high ratios, manifested by the flow and granular texture, as well as a higher melting temperature for the ‘33 / 67’-sample compared to when this sample is cooled rapidly.

[0168] Example 10 - Softener mixture of PCL polymer in moldable composition

[0169] In addition, different softeners can be added to the moldable composition. Table 11 lists the composition including PC and Benzoflex 988, in which the two softeners are melted and mixed into a uniform mixture. Expancel 461DE, Iokalit A and AK5 are added to the mixture and blended into a uniform moldable composition.

[0170] Table 11: Moldable compositions including two different softeners

[0171]

[0172] All three compositions were evaluated by melting in a 39°C water bath, then cooling to room temperature and solidifying. This process was repeated approximately 10 times. The "5% sample" and "10% sample" had stable properties, while the "50% sample" changed with increasing cycle number and eventually stopped melting at 39°C. This may reflect a change in composition due to the loss of PC, as this softener is quite soluble in water.

[0173] Example 11 - Loss of Softener in Mixture with PCL Polymer

[0174] A PCL (high Mw) / PC blend (33% / 67%) was prepared by melt mixing, formed into cubes (0.88 g), and cured by lowering the temperature. The perceived melting temperature of this "33 / 67" material may vary depending on the cooling rate, but the temperature is relatively low, about 30°C (Example 9).

[0175] The solid cubes were exposed to excess water (25°C) for 6 days and then left in air for another 7 days. After this treatment, the melting temperature of the material increased to about 60°C, which is similar to the melting temperature of pure PCL (high Mw) (i.e., "100 / 0" material).

[0176] This example illustrates that the loss of a water soluble softener can be used to increase the melt temperature and as a setting / hardening mechanism for the molded object. PC has a fairly high boiling point and low vapor pressure and does not lose a significant amount of softener by evaporation. It is expected that a PCL / PC blend will be storage stable prior to contact with water. Therefore, a PCL (high Mw) / DMC blend is less ideal and will "age" when exposed to air due to its lower boiling point (higher vapor pressure) compared to PC.

[0177] Example 12 - Surface treatment of sand filling material

[0178] A very suitable surface modified sand can be formed by treating sand or other silica containing fillers with 0.05 to 0.2% by weight of the filler of an alkoxysilane or silylalkanoate.

[0179] Table 12 - Materials

[0180]

[0181] The process time at production scale is largely determined by the time required to evaporate the water from the added silane solution / dispersion. Therefore, it is highly advantageous to minimize the amount of water required by increasing the concentration of silane in the aqueous solution / dispersion without compromising the surface treatment effect.

[0182] Mam1s sand is heated in a jacketed steam heated mixer to 55-60° C. The batch size on production scale is 400 kg.

[0183] A crude aqueous silane dispersion is prepared by vigorous mixing for 30-60 minutes. The pH is adjusted to about 4 with acetic acid, where the silane is least reactive. This provides a dispersion in which the silane does not react until it encounters the silanol groups on the sand surface, and the aqueous phase is evaporated.

[0184] The dispersion is then added to the preheated sand and mixing is continued until the water evaporates. When the sand is dry, the process is considered complete. The process time for large-scale production is about 5-30 minutes (varies depending on the amount of water used in the dispersion).

[0185] Table 13 lists the composition of the silane dispersions used for the 400 kg test. The two versions of the silane dispersions, 5% wt and 11% wt, were evaluated for sand properties using the following methods with good results. Version B is recommended for large-scale production as it contains less silane (XL10 and BS1701) and water and requires less processing time. Compared to version A, the water content is reduced by 74% and the degree of modification is increased from 17 mg per m 2 (17mg / m 2 ) down to 9 mg / m 2 (9mg / m 2 ).

[0186] Table 13A – Version A

[0187]

[0188] Table 13B – Version B

[0189]

[0190] The properties of the treated sand are judged by contacting the sand with pure water. An increase in the hydrophobicity of the particles confirms the modification. This is assessed by subjectively judging wettability and contact angle by contacting the sand with water. It is also possible to spread the sand on a flat surface and then place a drop of water on top of the sand. If the water rests on top of the sand in the form of a drop / lens without wetting the sand, the surface modification is considered successful. Another method is to pour the modified / treated sand into a large amount of water. If the sand immersed in the water clumps and is not wetted by the water, or if the sand particles are small (about 100 microns or less) and float on the water surface, the treatment is considered successful. Suboptimal treatment is characterized by sand being wetted by water, not clumping, and small sand particles sinking.

Claims

1. A composition comprising: a) at least one polyester homopolymer or copolymer having a melting point of 40°C to 70°C; and b) at least one softening agent having a molecular weight of 50 to 500 amu; wherein the melting point or softening point of the composition is in the range of 30-45°C; wherein the weight of component a) accounts for 25 wt% to 95 wt% of component a) and component b); and The weight of component b) accounts for 5 wt% to 75 wt% of component a) and component b).

2. The composition according to claim 1, further comprising: c) at least one filler.

3. A composition according to claim 2, wherein The at least one polyester homopolymer or copolymer comprises at least one homopolymer or copolymer of caprolactone.

4. A composition according to any one of the preceding claims, wherein The at least one polyester homopolymer or copolymer comprises at least one copolymer of caprolactone and lactide.

5. A composition according to any one of the preceding claims, wherein The at least one polyester homopolymer or copolymer comprises at least one homopolymer or copolymer of caprolactone having an average molecular weight of 10,000 to 120,000, preferably 20,000 to 100,000.

6. A composition according to any one of the preceding claims, wherein The softener comprises at least one alcohol; at least one carbonyl group; at least one ether; at least one organic acid; at least one halogen; at least one nitro group and / or at least one aromatic group.

7. A composition according to any one of the preceding claims, wherein The softener comprises at least one benzyl alcohol, benzyl ester, benzyl ether and / or benzoyl moiety, which is optionally substituted with at least one alcohol, at least one carbonyl group, at least one ether, at least one organic acid, at least one halogen and / or at least one nitro group.

8. A composition according to any one of the preceding claims, wherein The softener comprises at least one compound represented by formula (i) in: R1 and R2 are each independently selected from H, Cl, F, Br, NO2, CH3, C2 to C8 branched or straight chain alkyl or alkenyl; Each R3 and R4 is independently selected from H, Cl, F, Br, CH3, C2 to C8 branched or straight chain alkyl or alkenyl; m is an integer value between 1 and 10; and n is an integer value between 1-10.

9. The composition according to claim 8, wherein: R1 and R2 are each independently selected from H, CH3, C2 to C4 branched or straight chain alkyl or alkenyl; and mixtures thereof; Each R3 and R4 is H; m is an integer value between 2 and 3; and n is an integer value between 2-3.

10. The composition according to claim 6, wherein The carbonyl moiety is a carbonate.

11. A composition according to any one of the preceding claims, wherein The softener comprises at least one carbonate compound selected from: C2 to C 12 Cyclic carbonates; A linear alkyl carbonate of the formula R5-O-CO-O-R6, wherein R5 and R6 are independently C1 to C 12 Linear branched alkyl; An aryl carbonate of the formula R7-O-CO-O-R8, wherein R7 and R8 are independently C5 to C 10 aryl or heteroaryl; and C2-C 12 Dialkyl dicarbonates.

12. The composition according to any one of claims 2 to 11, wherein Component c) includes sand fillers, glass fillers, polymer fillers, mineral fillers or mixtures thereof.

13. A composition according to any one of claims 2 to 12, wherein Component c) comprises at least one surface-treated filler.

14. The composition according to claim 13, wherein The surface treatment is a hydrophobic surface treatment.

15. The composition according to claim 13 or 14, wherein The surface treatment is treatment with at least one alkoxysilane and / or at least one silylalkanoate.

16. The composition according to any one of claims 10 to 15, wherein The polymer fillers include polystyrene beads, polyolefin beads, polyester beads, polyamide beads, expanded polystyrene beads and mixtures thereof.

17. The composition according to any one of claims 2 to 15, comprising component c) in an amount of 10 to 95 wt% of components a) and b) and c).

18. A composition according to any one of the preceding claims, further comprising: d) at least one silicone oil.

19. A composition according to any one of the preceding claims, further comprising at least one component, It is selected from: e) Pigments; f) Flashing agent; g) mica or coated mica; h) perfume; i) Preservatives.

20. A model compound comprising at least one composition according to any one of the preceding claims.

21. A method of forming the composition of any one of claims 1-19, comprising: I) heating component a) to a temperature of 30 to 70° C., II) mixed with component b); III) in the presence of component c) and / or components d) to h), optionally mixed with component c) and / or components d) to h); and IV) cooling the obtained mixture to room temperature; The steps I), II) and III) can be performed sequentially or simultaneously.

22. The method according to claim 21, which comprises heating and mixing components a) and b) above the melting temperature of component a), then mixing with component c) and / or components d)-h) in the presence of component c) and / or components d)-h), and cooling to normal temperature.

23. The method according to claim 22, wherein: Component c) is present and the method comprises mixing component c) with component b), then heating and mixing with component a), and cooling to ambient temperature.

24. A method of forming a three-dimensional shape, comprising: i) warming the composition according to any one of claims 1 to 16 in water, wherein the temperature of the water is not greater than 42° C.; ii) forming the composition into a desired shape (e.g. by molding, extruding, rolling or freehand shaping); and iii) cooling the composition (eg, in ambient air, in ambient water, in chilled air, or in chilled water).

Citation Information

Patent Citations

  • Play modeling dough

    EP2646996A2

  • Modeling dough

    US5498645A

  • Material composition

    WO2006101440A1